Field dependent-independent cognitive style as a predictor of malevolent creativity: a multifaceted approach - Pierpaolo Zivi; Marco Giancola; Raffaella Nori; Laura Piccardi; Laura Piccardi; Simonetta D'Amico; Massimiliano Palmiero (Frontiers in Psychology)
IntroductionResearch interest in the intentionally harmful use of creativity, also known as malevolent creativity, is growing rapidly. However, the cognitive and individual underpinnings of malevolent creativity are still unclear. By employing a multifaceted approach, field dependent-independent cognitive style (FDI) was investigated as a potential individual component that may predict the likelihood of generating malevolent ideas (i.e., creative process), products (i.e., creative production), and engaging in original but malicious acts (i.e., creative behavior).MethodsBased on the literature associating FDI with general creativity, the hypothesis that field-independent individuals were more prone to the three facets of malevolent creativity was tested after controlling for demographic factors, social desirability, state mood, and ethical positions (idealism and relativism). Malevolent creativity was assessed through a divergent thinking task (process), a solicitation to produce black humor by a cartoon captions task (product), and a self-reported questionnaire concerning everyday creative acts (behavior).ResultsThe results showed that higher levels of field independence predicted malevolent creative process and product, whereas no differences emerged in creative behavior.DiscussionBy partially replicating the evidence connecting FDI and creativity, the present study suggests that general and malevolent creativity share common grounds. Future studies are needed to overcome the current limitations in assessing malevolent creativity in everyday settings and to investigate further commonalities and differences between the two uses of creativity.